2005
DOI: 10.3386/w11484
|View full text |Cite
|
Sign up to set email alerts
|

Political Competition and Economic Performance: Theory and Evidence from the United States

Abstract: One of the most cherished propositions in economics is that market competition by and large raises consumer welfare. But whether political competition has similarly virtuous consequences is far less discussed. This paper formulates a model to explain why political competition may enhance economic performance and uses the United States as a testing ground for the model's implications.It finds statistically robust evidence that political competition has quantitatively important effects on state income growth, st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
119
0
3

Year Published

2006
2006
2015
2015

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 86 publications
(124 citation statements)
references
References 12 publications
2
119
0
3
Order By: Relevance
“…5 2 This result is consistent with earlier work analysing the relationship between political competition and policy outcomes. For example, recent work by Besley and Case (2003) and Besley et al (2005) …nd that increased political competition leads to lower taxes. However, according to our de…nition, municipalities with a weak majority include unde…ned party coalitions, where neither the left-nor the right-wing bloc is in power, which is typically the case when there are strong local parties.…”
Section: Testing For Yardstick Competition E¤ectsmentioning
confidence: 99%
“…5 2 This result is consistent with earlier work analysing the relationship between political competition and policy outcomes. For example, recent work by Besley and Case (2003) and Besley et al (2005) …nd that increased political competition leads to lower taxes. However, according to our de…nition, municipalities with a weak majority include unde…ned party coalitions, where neither the left-nor the right-wing bloc is in power, which is typically the case when there are strong local parties.…”
Section: Testing For Yardstick Competition E¤ectsmentioning
confidence: 99%
“…8 It is expected, that high political concentration points to low political competition and thus should reduce efficiency (see e.g. Besley, Persson and Sturm, 2005). As a measure of political preferences, the share of seats of the left-wing parties (i.e.…”
Section: Datamentioning
confidence: 99%
“…In most theoretical models, this is modeled as rents that accrue to the politician or the political party in power (see transfers and slack and inefficiencies in policy making (Besley et al, 2007, Besley and Case, 2003and Svaleryd and Vlachos, 2007. Another way to further one's own interest is to make policy choices according to one's own preferences.…”
Section: Political Competition and The Impact Of Women's Representationmentioning
confidence: 99%
“…Empirical literature has found that strong political competition seems to keep politicians in power from furthering their own interests, rather than the interests of the general public (see e.g. Kalt and Zupan, 1984, 1990, Besley et al, 2007, Besley and Case, 2003and Svaleryd and Vlachos, 2007. This paper also provides evidence suggesting that political competition limits elected representatives from pursuing their own interest by showing that the effect of women's representation is smaller when political competition is strong.…”
Section: Introductionmentioning
confidence: 99%